Combinar leitura e “leitura”: ler, extrair, interpretar, visualizar - Rua, Joana (MATLIT: Materialities of Literature, 2020)
Recensão crítica de Martin Paul Eve. Close Reading with Computers: Textual Scholarship, Computational Formalism, and David Mitchell’s Cloud Atlas. California: Stanford University Press, 2019. 272 pp. ISBN: 9781503609365.